THE EFFECT OF CUSTOMER EXPERIENCE AND FEAR OF MISSING OUT (FOMO) ON REPURCHASE INTENTION THROUGH CUSTOMER TRUST AS AN INTERVENTION VARIABLE (SKINTIFIC CUSHIONE SURVEY ON SHOPEE) - Rika Aulia; Nurul Komariyatin (MANAJEMEN DEWANTARA, 2025)
In addition to its significant market potential, the Indonesian cosmetics industry is also a highly sought-after sector by domestic players, as it competes with various international brands. This intensifies competition and encourages cosmetics companies, particularly local producers, to stand out in the eyes of potential consumers, ultimately leading to repeat purchases, transacting with a particular company, and becoming its customers. This study aims to determine the influence of customer experience and brand image, as well as FEAR OF MISSING OUT (FOMO), on repurchase intention for a skintific cushion product on the Shopee platform, mediated by cstomer trust. This study used PLS-SEM as the analysis technique and was processed using SmartPLS software version 4.0. The results of the analysis indicate that: Based on the data above, the analysis results indicate that customer experience and FEAR OF MISSING OUT (FOMO) influence repurchase intention, with customer trust as an intervening variable.